Development of multifunction ladder - Nurul Jasmie, Che Ahamed (2009)
The objective of this thesis is to develop and fabricate the multifunction ladder and to minimize the manufacturing cost. Ladder is equipment that can easier consumer’s daily activities at higher place. It is stable and safe to use. The concept of this project is based on student’s creativity. The characteristics of material to fabricate this ladder are lightweight, longer life span, corrosion resistance and can take maximum load. Thus, the suitable material that accomplished those characteristics is aluminium alloy. In this thesis, we’ll also be having more to the fabrication of this ladder.